Associational susceptibility of crop plants caused by the invasive weed Canadian goldenrod, Solidago canadensis, via local aphid species - Szabó, Attila-Károly; Bálint, János; Molnár, Attila; Aszalos, Szilvia Erzsébet; Fora, Ciprian George; Loxdale, Hugh David; Balog, Adalbert (Frontiers in Ecology and Evolution, 2022)
In the present study, field surveys were conducted to detect potential associational susceptibility of crop plants (potato, alfalfa and maize) caused by Canadian goldenrod, Solidago canadensis (L.), one of the most common invasive weeds in Central and Eastern Europe through plant associated virus vectoring aphids. Assessments were made in two major agricultural land types: crops grown under high input (HIF) vs. low-input (LIF) conditions, with and without fertilizers and pesticides. The two most frequent aphid species found both on Canadian goldenrod and crop plants were the leaf-curling plum aphid, Brachycaudus helichrysi Kaltenbach and the glasshouse-potato aphid, Aulacorthum solani (Kaltenbach). Plant viruses in both weed and crop plants were identified using high-throughput sequencing of small RNAs. Peroxidase (POD) enzyme activity was tested in weed and crop plants to connect aphids feeding processes in weeds and crops. In addition, conceptual modelling was used to detect direct relationships between viruses and other crops. The Canadian goldenrod density was only relevant in the LIF regime. Furthermore, its association with B. helichrysi and associational susceptibility was detected only in LIF. In total, 18 viruses comprising 17 plant and one insect virus were detected in Canadian goldenrod, of which 11 were also detected in potato and alfalfa crops. POD activity was high and correlated with high aphid density in both weed and crop plants, suggesting a direct associational susceptibility between these plants through aphid infestation and viral transmission.